The Differences of Student’s learning interest from specialization MIA in Private schools and public schools - Nadya Ardi; Yusri Yusri (Jurnal Neo Konseling, 2019)
Learning is a process carried out by someone in obtaining a change in behavior as a whole, as a result of interaction with the environment. Related to learning interest is something that is related to individuals in meeting their needs through activities. The interest in learning referred to in this study is a sense of pleasure in learning, interest in learning, attention in learning, and involvement in learning. This study aims to examine whether there are differences in students' interest in studying Mathematics and Natural Sciences (MIA) in public and private schools. Sampling in this study using proporsioal  random sampling technique with a total sample of 154 students. The research instrument used was a student interest questionnaire. The results of the study use that (1) the level of interest in learning MIA specialization in public schools is in the high category (2) the level of interest in learning in MIA specialization in private schools is in the high category (3) there is no significant difference between the learning interests of MIA specialization students in schools public and private schools.